2023
DOI: 10.1186/s13046-022-02581-1
|View full text |Cite
|
Sign up to set email alerts
|

The N6-methyladenosine METTL3 regulates tumorigenesis and glycolysis by mediating m6A methylation of the tumor suppressor LATS1 in breast cancer

Abstract: Background Posttranscriptional modification of tumor-associated factors plays a pivotal role in breast cancer progression. However, the underlying mechanism remains unknown. M6A modifications in cancer cells are dynamic and reversible and have been found to impact tumor initiation and progression through various mechanisms. In this study, we explored the regulatory mechanism of breast cancer cell proliferation and metabolism through m6A methylation in the Hippo pathway.  … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(29 citation statements)
references
References 21 publications
2
27
0
Order By: Relevance
“…METTL3, an important RNA methyltransferase, plays a critical role in RNA modification, and its expression and catalysed RNA m6A modification are associated with the occurrence and progression of various human diseases 10–12,14 . Prior studies have demonstrated that METTL3 is overexpressed in various cancers and contributes to cancer progression and metastasis 21,46–55 . In this study, we further confirmed through multi‐data set analysis that the expression of METTL3 was significantly higher in tumour samples than in the control group.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…METTL3, an important RNA methyltransferase, plays a critical role in RNA modification, and its expression and catalysed RNA m6A modification are associated with the occurrence and progression of various human diseases 10–12,14 . Prior studies have demonstrated that METTL3 is overexpressed in various cancers and contributes to cancer progression and metastasis 21,46–55 . In this study, we further confirmed through multi‐data set analysis that the expression of METTL3 was significantly higher in tumour samples than in the control group.…”
Section: Discussionsupporting
confidence: 76%
“…[10][11][12]14 Prior studies have demonstrated that METTL3 is overexpressed in various cancers and contributes to cancer progression and metastasis. 21,[46][47][48][49][50][51][52][53][54][55] In this study, we further confirmed through multi-data set analysis that the expression of METTL3 was significantly higher in tumour samples than in the control group. ROC results indicated that its expression the expression of ER target genes and limits the growth of breast cancer cells.…”
Section: Discussionsupporting
confidence: 75%
“…More and more studies have shown that METTL3 regulates mRNA stability through m6A methylation, thereby mediating cancer progression. For example, METTL3 decreased LATS1 mRNA expression in a m6A‐dependent manner, thereby accelerating breast cancer tumorigenesis and glycolysis 21 . Also, METTL3 promoted pancreatic cancer cell proliferation and stemness by increasing ID2 mRNA stability through m6A modification 22 .…”
Section: Discussionmentioning
confidence: 99%
“…It is known that upstream regulators of the Hippo pathway, such as mammalian Ste20‐like kinases 1/2 (MST1/2) and LATS1/2, converge at the downstream effectors, YAP1 and TAZ 41 . Previous studies have also demonstrated the oncogenic roles of MST1/2 42 and LATS1/2 43 in human tumours, including proliferation, apoptosis, and glucose metabolism. Furthermore, some other common kinases, such as epidermal growth factor receptor (EGFR) kinase, have also been correlated with autophagy 44 or glucose metabolism 45 in human diseases.…”
Section: Discussionmentioning
confidence: 99%